Abiotic Stress Responses in Plants 2011
DOI: 10.1007/978-1-4614-0634-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Fruit Production in Mediterranean Orchards Subjected to Drought Stress

Abstract: Drought stress is the main cause of reduced fruit tree growth and productivity in Mediterranean semi-arid regions and causes a complex of responses at molecular, cellular, physiological and developmental level. In particular, the response of fruit trees to water scarcity is a species-and cultivar-dependent and a series of studies have been carried out to clarify and deepen the mechanisms of their adaptation, avoidance, resistance or tolerance against drought. Considering that 16% of the total cultivable land o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 157 publications
(170 reference statements)
0
12
0
1
Order By: Relevance
“…Soil microorganisms' dynamics (e.g., mobility, growth, nutrient absorption, and respiration), the major responsible of soil fertility and quality (B€ unemann et al, 2018), are strongly affected both by the type of soil management and irrigation, and this has been widely demonstrated in fruit crops (Palese et al, 2009;Sofo et al, 2012Sofo et al, , 2014aPascazio et al, 2018). Soil microorganisms influence and, at the same time, are influenced by the soil C and N contents, being bacteria an essential part of C and, even more, of N-cycling processes (Zhang et al, 2014;Li et al, 2018).…”
Section: Soil Microbial Dynamics In Orchard Agrosystemsmentioning
confidence: 99%
“…Soil microorganisms' dynamics (e.g., mobility, growth, nutrient absorption, and respiration), the major responsible of soil fertility and quality (B€ unemann et al, 2018), are strongly affected both by the type of soil management and irrigation, and this has been widely demonstrated in fruit crops (Palese et al, 2009;Sofo et al, 2012Sofo et al, , 2014aPascazio et al, 2018). Soil microorganisms influence and, at the same time, are influenced by the soil C and N contents, being bacteria an essential part of C and, even more, of N-cycling processes (Zhang et al, 2014;Li et al, 2018).…”
Section: Soil Microbial Dynamics In Orchard Agrosystemsmentioning
confidence: 99%
“…Many tree fruit producing arid regions are typically exposed to elevated abiotic stress including high light intensity, temperature, and low rainfall that can affect crop yield and quality [3]. Most of these regions frequently rely on irrigation to provide an adequate water supply to maintain orchard productivity [4] and fruit quality [5]. These irrigation-dependent regions may experience higher risks from variations in water availability and elevated temperatures in the future [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on irrigation management under different agroecological system on fruit crops e.g. peach [2][3][4], cherry [5], pummelo [6], olive [7,8] and mango [9] reported that moderate water restriction do not effect morphological and physiological processes of tree. In fact, enhance the bearing, maturation and fruit tree features.…”
Section: Introductionmentioning
confidence: 99%